تأثير تكربن البيتون على ديمومة بعض الجسور الطرقية الواقعة في المنطقة الساحلية السورية - طريفي, زكائي; منصور, نزيـه; مـيا, عـلاء (Latakia University Journal -Engineering Sciences Series, 2019)
يعتبر صدأ فولاذ التسليح من أكثر أسباب تدهور المنشآت البيتونية المسلحة شيوعاً في الساحل السوري، ويمكن اعتبار تكربن البيتون أحد الأسباب الرئيسة لحدوث ذلك، كون الطبيعة المناخية في الساحل السوري تعتبر مساعدة على حدوث تكربن البيتون بمعدل عالٍ نسبياً. أجري في هذا البحث دراسة حقلية لعمق التكربن في ركائز عدد من الجسور الواقعة بين محافظتي طرطوس وحمص ، وتبين من خلال هذه الدراسة أن ركائز تلك الجسور تعاني من معدلٍ عالٍ لتكربن البيتون حيث كانت القيمة الوسطية لثابت نفاذية البيتون تساوي 5.461 mm/year0.5)) بالإضافة لوجود نقص واضح في سماكة طبقة التغطية البيتونية لفولاذ التسليح والتي كانت معدومة في عدد من الحالات، مما أدى أو قد يؤدي لاحقاً إلى صدأ فولاذ التسليح وما قد ينتج عن ذلك من تشققات وانسلاخات في البيتون أو فقدان السلامة الإنشائية للمنشأ على المدى الطويل. Corrosion of reinforcement steel is considered one of the most common reasons for reinforcement concrete structures deterioration in Syrian Coastal region. The main cause of this could be the concrete carbonation, due to the Syrian Costal region climate conditions which allows a high rate of carbonation process. In this field research a study was done on the pillars of a number of bridges located between Tartous and Homs. The results show that these pillars suffer from a high rate of carbonation (with an average value of about 5.461mm/year0.5 for concrete permeability constant), together with clear deficiency in the concrete cover thickness of the reinforcement bars, which may have caused, or might cause in the future, corrosion to the steel bars. This, in turn, might develop cracks and spalling in concrete cover and damage of these bridges' structural safety in the long term.